REKONSTRUKSI DOGMATIK ALASAN PENGHAPUS PIDANA ANTARA DIFERENSIASI OVERMACHT, NOODTOESTAND, DAN NOODWEER DALAM UNDANG-UNDANG NOMOR 1 TAHUN 2023 - Irsadi Aristora; Muhammad Ikhwan Adabi; Jalaluddin Jalaluddin; Rahmat Jhowanda; Nurmala Sari (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2026)
Previous criminal justice practices in Indonesia were hindered by the confusion of the colonial-inherited Criminal Code (WvS), which erroneously merged the State of Emergency (Noodtoestand) into the construction of Force Majeure/Duress (Overmacht). Recognizing this systematic flaw, Law Number 1 of 2023 concerning the National Criminal Code deconstructs this rule by independently separating Overmacht, Noodtoestand, and Self-Defense (Noodweer). This study is a normative legal research utilizing statutory, conceptual, and historical approaches. The results show two main findings. First, the ratio legis for this separation is rooted in the recognition of the legal subject's rationality. Overmacht is positioned purely as an excuse (schulduitsluitingsgrond) due to the paralysis of the perpetrator's free will under severe pressure, while Noodtoestand is recognized as a justification (rechtvaardigingsgrond) as it involves rational balancing (belangenafweging) strictly bound by the principles of subsidiarity and proportionality. Second, the differentiation of these three criminal defense grounds is based on four strict juridical parameters, including: the source of the threat, the condition of the perpetrator's free will, the target of the act (the injured party), and their dogmatic qualifications. Through this reconstruction, the New Criminal Code presents rigid legal certainty to minimize disparities in judicial decisions and guarantee substantive justice.